Involvement of NF-κB signaling pathway in the regulation of PRKAA1-mediated tumorigenesis in gastric cancer - Yangmei Zhang; Xichang Zhou; Qinglin Zhang; Youwei Zhang; Xiang Wang; Long Cheng (Artificial Cells, Nanomedicine, and Biotechnology)
AMP-activated alpha 1 catalytic subunit (PRKAA1) is one of the subunits of the mammalian 5′-AMP-activated protein kinase (AMPK) playing an important role in maintaining intracellular energy metabolism and associating with the risk of gastric cancer (GC). This paper aims to uncover the influences of PRKAA1 on the tumorigenesis of GC, as well as the underlying mechanisms. We found that Helicobacter pylori (H. pylori) infection markedly increased p-NF-κBp50 and NF-κBp50 expression, along with the PRKAA1 expression, which was inhibited by NF-κBp50 knockdown. NF-κBp50 and PRKAA1 expression were lower in non-tumor gastric tissues compared with that in GC tumor tissues. Up-regulation of PRKAA1 expression was correlated with poor survival in GC patients. MKN-45 and BGC-823 cells stably knockdown of PRKAA1 were transplanted into nude mice and observed the decreased cell metastasis in the lungs. PRKAA1 knockdown in GC cells showed significant decreases in the cell invasion and migration and inhibited MMP-2 expression and NF-κB activation, whereas PRKAA1 involved in NF-κBp50 mediated GC cell invasion and migration. In conclusion, our findings suggest the involvement of NF-κBp50 in the regulation of PRKAA1 in GC tumorigenesis.